Segesta riograndensis, new genus and species of an Atalophlebiinae (Ephemeroptera: Leptophlebiidae) mayfly from southern Brazil - Siegloch, Ana E.; Polegatto, Cleber M.; Froehlich, Claudio G. (Zootaxa, 2006)
A new genus, Segesta, is described based on nymphs from the State of Rio Grande do Sul, southern Brazil. The genus is related to Thraulodes, Massartellopsis, Meridialaris and Secochela as indicated by the posterolateral spines on abdominal segments 2 to 9, by the long lanceolate gills present on segments 1 to 7, tarsal claws without a large subapical denticle, and general shape of clypeus and labrum. However, the new genus can be distinguished from those related genera by the maxillary and labial palps that are very large and remarkably curved, a shape unique among the Neotropical Atalophlebiinae not belonging to the Hermanella-group.